The effect of infliximab and octreotide on cytokine levels experimental proliferative vitreoretinopathy - Savur, Fatma; Aydemir, Orhan; Ilhan, Nevin (Taylor & Francis Ltd, 2020)
Purpose: To investigate the efficiency of intravitreal octreotide, which has previously been shown to have benefits in the treatment of proliferative vitreoretinopathy (PVR), and intravitreal infliximab as a novel option in an experimental dispase-induced PVR model. Methods: A total of 28 pigmented guinea pigs were divided into four groups, and each group consisted of seven subjects. Group 1 (control) was treated with a 0.2 mL saline solution intravitreally from 1.5 mm behind the limbus. Group 2 (sham) was treated with 0.07 IU/0.1 mL dispase 0.1 mL saline solution using the same method. Group 3(infliximab) received 0.07 IU/0.1 mL dispase and 1 mg/0.1 mL infliximab, and group 4(octreotide) was treated with 0.07 IU/0.1 mL dispase and 1 mg/0.1 mL octreotide. An intravitreal injection of infliximab and octreotide was administered to groups 3 and 4 two times during the experiment. The subjects were held for a 10-week period to await for the formation of PVR. At the end of ten weeks, the eyes were enucleated, and tumour necrosis factor-alpha (TNF-alpha), interleukin 1(IL-1), interleukin 6 (IL-6), transforming growth factor (TGF-beta), and platelet-derived growth factor (PDGF) and levels in homogenised retina tissue were measured using the enzyme linked-immuno-sorbent assay (ELISA) method. Results: Retinal TNF-alpha, IL-1, IL-6, and PDGF levels had significantly decreased in treatment groups compared to the sham group (p < 0.05). The decrease in the level of TGF-beta was not statistically significant between the treatment and the sham groups (p > 0.05). Conclusions: Intravitreal infliximab can inhibit the development of PVR and reduce levels of cytokine, which plays an essential role in the pathogenesis of PVR. The results of our study suggest that it may be possible to identify the ideal adjuvant pharmacological drugs that are effective in preventing PVR.
Keywords: Dispase; infliximab; octreotide; proliferative vitreoretinopathy